The Investigation of Therapeutic Implications of Mast Cell Stabilizer Cromolyn Sodium on Cholestasis and Cholestatic Pruritus in Experimental Cholestasis - Yurdakul Ertan, Hanife; Özbakış Dengiz, Günnur; Barut, Figen; Yılmaz Ürün, Yonca; Can, Murat; Umer Hussen, Shemsu; Üstündağ, Yücel (Turkish Journal of Gastroenterology, 2022)
Background: Relevant studies have indicated that hepatic mast cells may have potential roles in the progression of cholestasis and cholestasis-induced itch. We aimed to compare the effects of cromolyn sodium and other medications on cholestatic pruritus, serum biochemistry, histamine, total bile acids, autotaxin, liver histopathology, and mast cell distribution in tissues in an experimental cholestasis model conducted by bile duct ligation. Methods: Rats received the determined treatment consecutively for 10 days in addition to bile duct ligation. On the 5th and 10th days of the experiment, the rats’ itching behaviors were observed for 5 minutes. After 10 days, blood and tissue samples were taken. Results: Significant decreases in serum histamine and autotaxin levels, plasma total bile acids, total bilirubin, and biliary enzymes were reported only in cromolyn sodium-treated rats compared to the control group. In immunohistochemistry of the liver samples, the peribiliary mast cells stained positive for autotaxin. Except for bile duct infarctus, all histopathological findings of cholestasis significantly improved only in cromolyn sodium-treated and sertraline-treated rats. The liver and peritoneal mast cells significantly decreased only in cromolyn sodium-treated rats compared to the control group. On the 10th day of the experiment, the mean duration of itching was significantly lower in all groups, except for naloxone- and ondansetron-treated rats. Conclusion: Cromolyn sodium has promising antipruritic efficacy and provides biochemical and histopathological recovery of the relevant parameters of cholestasis induced by bile duct ligation. For the first time in the literature, we showed that peribiliary mast cells can produce autotaxin, which is a very important pruritogenic signal in the setting of cholestasis. Cite this article as: Yurdakul Ertan H, Özbakış Dengiz G, Barut F, et al. The investigation of therapeutic implications of mast cell stabilizer cromolyn sodium on cholestasis and cholestatic pruritus in experimental cholestasis. Turk J Gastroenterol. 2023; 34(1): 62-72.